Pemanfaatan Youtube Sebagai Media Peningkatan Pelayanan Dan Informasi - Suharsono, Jatra Putra; Nurahman, Dwi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to explore and analyze the use of YouTube as a medium to improve services and disseminate information. By focusing on relevant literature, this research tries to understand how YouTube has become an effective platform in expanding the reach of information and improving the quality of services provided. The literature study method was used to collect and analyze various articles, books and other sources related to the use of YouTube in the context of providing information. Research findings show that YouTube has become one of the main tools in disseminating information widely and enabling service providers to interact directly with their audiences. The analysis also reveals that the use of YouTube in improving services can include various strategies, such as tutorials, vlogs, webinars and other interactive content. Additionally, this research highlights the importance of understanding audience characteristics and trends in YouTube usage to present relevant and engaging information. In this context, this research provides valuable insights for practitioners and researchers to understand the full potential of YouTube as a medium for improving services and disseminating information. The practical and theoretical implications of these findings are discussed, as well as directions for further research in exploring the role of YouTube in the context of information communication and public services.